Can Small Class Policy Close the Gap? An Empirical Analysis of Class Size Effects in Japan1. (1st July 2013) - Akabayashi, Hideo; Nakamura, Ryosuke
<x xml:space="preserve">Abstract</x> Can smaller classes lead to better educational outcomes and greater equality in achievement? We estimate the causal effects of class size on achievement tests by using discontinuous changes in class size under the Japanese public compulsory education system. We employ a value‐added model that uses achievement tests conducted at two different times during the same school year. Our results show that a reduction in class size has significantly positive effects on Japanese language test scores in the sixth grade, especially at schools in wealthy areas. However, we find no evidence that a universal small class policy closes the achievement gap among schools.